Dampak Pariwisata Telaga Ngebel terhadap Ekonomi dan Sosial Budaya Masyarakat Lokal - Sehlfi Ma’rifatil Laili; Sabda Elisa Priyanto; Maya Dewi Savitri; Dyah Wahyuning Tyas (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
This study aims to analyze the impact of tourism in Telaga Ngebel, Ponorogo Regency, on the income of the local community and the socio-cultural changes that occur. Using a qualitative approach, data were collected through in-depth interviews and field observations conducted in March–April 2025. Data analysis was performed using the Miles and Huberman interactive model, strengthened through source and method triangulation. From an economic perspective, the findings show that the increase in the number of tourists has a significant contribution to the rise in local income. This condition encourages the development of entrepreneurial activities through the establishment of new businesses, both in the informal sector (street vendors) and formal sector (hotels and food services). This development has led to job creation and improved economic well-being for the community. From a socio-cultural perspective, tourism functions as a means of promoting local culture, including arts, traditions, and regional cuisine. Interactions with tourists also raise the awareness and pride of the community toward their cultural heritage, which indirectly supports preservation efforts. However, the study also found that some members of the community resist change, choosing to maintain local traditions and values amidst the flow of modernization.